Physical manipulation of biological and chemical syntheses for nanoparticle shape and size control - Ogale, Satishchandra B.; Ahmad, Absar; Pasricha, R.; Dhas, Vivek V.; Syed, A. (Applied Physics Letters, 2006)
A nanosynthesis scheme is demonstrated which renders excellent control of nanoparticle shape, size, and dispersity in a solution based synthesis process. The scheme, termed as percolative microcavity synthesis, involves the use of a granular medium with percolative microcavities which facilitate nearly similar grain size/shape dependent reaction zones limiting intrinsic growth inhomogeneities, enabling particle size/shape control. The viability of the process is demonstrated for the synthesis of gold nanoparticles by a plant extract based biological method as well as a chemical method. (c) 2006 American Institute of Physics.

Fungus-based synthesis of chemically difficult-to-synthesize multifunctional nanoparticles of CuAlO2 - Ahmad, Absar; Jagadale, Tushar C.; Dhas, Vivek V.; Khan, Shadab; Patil, Shankar; Pasricha, Renu; Ravi, Venkat; Ogale, Satishchandra B. (Advanced Materials, 2007)
Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 degrees C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein-capped water-dispersible nanoparticles show blue luminescence and radio-frequency absorption (see figure).

Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Shape preserving chemical transformation of ZnO mesostructures into anatase TiO2 mesostructures for optoelectronic applications - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Yengantiwar, Ashish; Ogale, Satishchandra B. (Energy & Environmental Science, 2011)
In this work we report on the synthesis of various ZnO mesostructures (rods, spheres, flakes and flower-like morphologies) by hydrothermal and co-precipitation methods and their remarkable and complete transformation into anatase TiO2 mesostructures with nominally similar shapes using controlled low temperature TiCl4 treatment. Various techniques are used to demonstrate the phase purity and morphology details. Based on the careful examination of the transformation of ZnO rods into TiO2 tubes we suggest a mechanism which embodies initial formation of a thin TiO2 shell on the ZnO surface by ion exchange (Ti4+-Zn2+) followed by Zn diffusion through the shell and its oxidation on the surface. We used these converted TiO2 mesostructures for light harvesting in Dye Sensitized Solar Cells (DSSCs) to enhance the conversion efficiency. It is shown that DSSCs made using a doctor bladed film of TiO2 nanoparticles with an overlayer of TiCl4 treated ZnO flowers yield a solar cell efficiency of 6.9% which is considerably higher than that with only TiO2 nanoparticle film (5.4%) of comparable thickness.

Dye sensitized solar cell (DSSC) by a novel fully room temperature process: a solar paint for smart windows and flexible substrates - Agarkar, Shruti A.; Dhas, Vivek V.; Muduli, Subas; Ogale, Satishchandra B. (RSC Advances, 2012)
We report the development of a titania-nanoparticle-based solar paint which gives a conversion efficiency of 3.6% on FTO/glass substrates under fully room temperature processing. The paint cures quickly saving time in the cell fabrication process. Even on a flexible ITO/PET substrate efficiency of 2.4% was achieved. We present and analyze the results of described materials and device property characterizations.

TiO2-Au plasmonic nanocomposite for enhanced dye-sensitized solar cell (DSSC) performance - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Vijayamohanan, K.; Bogle, Kashinath A.; Valanoor, N.; Ogale, Satishchandra B. (Solar Energy, 2012)
Anatase TiO2 nanoparticles dressed with gold nanoparticles were synthesized by hydrothermal process by using mixed precursor and controlled conditions. Diffused Reflectance Spectra (DRS) reveal that in addition to the expected TiO2 interband absorption below 360 nm gold surface plasmon feature occurs near 564 nm. It is shown that the dye sensitized solar cells made using TiO2-Au plasmonic nanocomposite yield superior performance with conversion efficiency (CE) of similar to 6% (no light harvesting), current density (J(SC)) of similar to 13.2 mA/cm(2), open circuit voltage (V-oc) of similar to 0.74 V and fill factor (FF) 0.61; considerably better than that with only TiO2 nanoparticles (CE similar to 5%, J(SC) similar to 12.6 mA/cm(2), V-oc similar to 0.70 V, FF similar to 0.56). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Anatase TiO2; Au; Dye-sensitized solar cells; Hybrid composite; hydrothermal